Tipos de tutorados y su influencia sobre las características agronómicas y rendimiento de Solanum lycopersicum L., var. "tomate regional", en Zungarococha-Loreto.2021 - Gutierrez Arevalo, Alonso (2022)
The experiment "types of tutors and their influence on the agronomic characteristics and yield of solanum lycopersicum L. var. " regional tomato", in zungarococha-loreto.2021, was held at the facilities of the Workshop on Teaching and Research of Horticultural Plants (TEIPH), of the Faculty of Agronomy-UNAP, located south of the city of Iquitos. The type of research was experimental, explanatory with an independent variable (Types of tutors) and eight dependent variables (plant height, fruit length, fruit diameter, number of fruits/plant, fruit weight, fruit weight/plant and fruit weight/ha). The objective of the research work was to determine the influence of the types of tutors on the agronomic characteristics and yield of Solanum lycopersicum L., var. "regional tomato", in Zungarococha in Zungarococha-Loreto.2021. The experimental design that was used was the Completely Random Block Design, with four treatments and four repetitions. Each experimental unit consisted of 2 rows, 10 plants/row and the sampling unit consisted of four plants/experimental unit. At the end of the experiment, the following conclusions were reached: The type of tutoring influences the agronomic characteristics and yield of Solanum lycopersicum L., var. "regional tomato"; the tutor of greatest influence in the length of the fruit were the vine type and the individual stake type, in the diameter of the fruit was the vine type and the height of the plant were the trellis type and the pyramidal type; the tutoring of greater influence on the yield of fruit weight, weight of fruits / plant and weight of fruits / ha was the vine type (T4) and in the number of fruits / plant was the pyramidal type (T3); The tutoring with the best yield of fruit weight/ha was the vine type with 25,056 t/ha (T4); The tutor with the best economic performance was the vine type (T4), with a utility of S/.35,922.00.